KORELASI MOTIVASI DENGAN HASIL BELAJAR SELAMA PANDEMI COVID 19 PADA PESERTA DIDIK KELAS MIA XI - Nurfathurrahmah Nurfathurrahmah; Ariyansyah Ariyansyah; Erni Suryani; Olahairullah Olahairullah (Jurnal Biotek, 2021)
The learning process is undertaken both online and face-to-face during the pandemic. But it is constrained by time constraints and physical distance. As a result, student motivation and learning results are affected. This ex post facto research aimed to correlate the motivation toward learning outcomes during the covid-19 pandemic in MIA XI class students. The number of samples was 24 students from all 3 MIA XI classes using the Non-Random Sample technique. The instruments were a questionnaire sheet and an essay test. Data were analyzed using the product-moment correlation formula as SPSS 16.0 application for windows. The results of data analysis show that the value of rcount is smaller than rtable (0.196 < 0.404), then the null hypothesis (H0) in this study is accepted and the working hypothesis (H1) is rejected. The correlation number from product-moment correlation analysis is 0.196. Based on the interpretation of the correlation coefficient. 0.00 - 0.199 means a very weak relationship. It appears that the correlation of motivation with learning outcomes during the covid 19 pandemic in MIA XI class students is weak. In other words, the correlation between motivation and learning outcomes can be influenced by many factors. The factors could be an online learning system, teaching methods, learning intensity, interests, learning resources, school environment, and family.